E-Marketing Model at Bali Chaya Kuta Hotel in The New Normal Era - Selamet, Wayan Agus; Dewi Prihantari, Gusti Ayu Putu Eka (Akademi Komunitas MAPINDO, 2022)
This study aims to analyze the e-marketing model applied to Hotel Bali Chaya Kuta from the time before the Covid-19 pandemic to the New Normal era. This is to analyze the right e-marketing model that can be used during the new normal era. The method used in this study is a qualitative descriptive methode with data collection techniques used consisting of observations, interviews, and documentation with data validation using focus group discussions. The informant retrieval technique in this study used porposive sampling. Activities in qualitative data analysis, namely data reduction, display data, and conclusion drawing/verification. The results of the data analysis are known to be the e-marketing model applied in the new normal era on social media with three stages, namely the components of social media marketing that can be applied in the future: Customer Engagement, Influence, Online Community. Marketing communication through online travel agents has four marketing components that can be used in online travel agents which include Promo, Information, Respond to market, Review. Marketing through websites is divided into four dimensions, namely: Content, Branding, Disign, SEO (Search Engine Optimization). Keywords: E-marketing Model, New normal